DAMPAK NEGATIF HASAD DAN DENGKI TERHADAP KESEHATAN (STUDI ANALISIS DALAM PERSPEKTIF HADIS) - Alwan Amir Damanik (SHAHIH (Jurnal Ilmu Kewahyuan), 2025)
This study examines the negative impacts of hasad (envy) and spite on human health through an analysis of the Hadith perspective. Hasad and spite are not merely diseases of the heart that destroy spiritual deeds, but they also have a significant adverse effect on an individual's physical and mental health. The primary objective of this research is to identify and analyze the various health impacts arising from these traits using a Hadith study approach. The research method employed is qualitative, specifically library research. Primary data are sourced from authentic Hadith books such as Sahih Bukhari and Sahih Muslim, while secondary data are obtained from health literature, journals, and Islamic psychotherapy books. The results indicate a strong correlation between hasad and various health disorders. In the perspective of Hadith, hasad is likened to fire consuming firewood due to its destructive nature. Medically and psychologically, this trait triggers the excessive production of stress hormones (cortisol and adrenaline), which can lead to insomnia, high blood pressure, gastric disorders, chest pain, and a weakened immune system. Furthermore, hasad contributes to premature aging, characterized by facial wrinkles and the early growth of gray hair. This study concludes that Islam provides comprehensive solutions to overcome these heart diseases through strengthening faith, gratitude, increasing istighfar (seeking forgiveness), and performing acts of worship such as prayer and zakat (almsgiving) to purify the soul. The implementation of these teachings is proven effective in maintaining holistic human health, both from spiritual and physical aspects.